India - Urban Finance and Governance Review : Volume 1. Executive Summary and Main Report - World Bank (Washington DC, 2013)
The report makes an in depth analysis of what to expect of future urban population growth in cities across India. Cities play a critical role in India's development. While its one billion-plus population is predominantly rural, over 300 million people live in urban areas. One-third of this population lives in 35 urban agglomerations or cities exceeding one million. Cities' governments are responsible for delivering various public services, yet severe infrastructures shortages in water supply and sanitation, roads, transportation, housing and waste management, and inefficient management have resulted in poor quality services. These inadequate services and worsening environmental conditions affect the poor. Between 1950 and 2000 India's urban population increased from 62 to 288 million. Already strained to provide services and quality of life to existing urban residents, cities will face tremendous challenges in expanding existing infrastructure and avoiding deterioration of living standards due to congestion, pollution, and lack of basic services. A doubling of the population over 30 years means that by 2030 there will be a second Mumbai, a second Calcutta, and a second Bangalore that must be fed, supplied with water, sanitation, electricity, give public and private transportation options; and where garbage must be disposed of. The report concludes by laying out a series of state and local actions over the short-medium and long-term to enhance fiscal sustainability and strengthening institutional capacity building of state and local governments.